The aesthetics of immersion : time, process and performance in practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Munnelly, Lisa (Massey University, 2003)
The initial impetus for this inquiry stemmed from a visit to the group multimedia exhibition entitled 'In the Shed.com', which was part of the Wellington Fringe Festival in 2001 What particularly struck me with this show (described as an interactive upload of image layers and process) was how the paintings in it were completely overwhelmed by the accompanying digital projections. With this in mind I returned home later that night watch the current affairs show.'Nightline'.which previewed another exhibition on in town. The camera accompanied by some upbeat techno mix swooped, spun, jerked and ducked as if the cameraman was more inspired by the soundtrack than the work, which hung on the wall impassive, or helpless in its attempts to arrest the darting gaze of the camera. On reflection, I saw in this an alignment to Walter Benjamin's views that 'the masses seek distraction whereas art demands concentration from the spectator'.(Arendt 1970:241). Studies on perception which show that motion has the greatest appeal to our senses led me to pose the question; how could the static artwork compete against the innate attraction of the moving image? Theories around what is called the "aesthetic experience" point out, that for a viewer to really engage with an artwork, the information contained within it must engage with information already stored in the viewer's mind. I saw this strategy being employed by artists such as Cindy Sherman and Peter Doig, whose work plays with the well known imagery of classic film genres, acting as contemporary versions of historical painting which portrayed widely known religious grand narratives. However the strategy of using a pictorial narrative to hold the viewer's attention in my own work became problematic as the question of what to show became overpowering. To free my work from such pictorial subservience, I turned to minimalist and process art practices for inspiration.Following the likes of the artist Lee Lozano, I drew up an action plan of verbs; scratch, pour, layer, stack etc, and applied them to different media. Being engrossed in the physicality of different materials acted as a release from the constant decision making element of artistic production, while a prior acceptance that these action pieces were explorations rather than arrivals absolved me of the responsibility of needing to know the end before I'd even begun, thus allowing for the new and unexpected.
Keywords: Process art; Art; Philosophy; Aesthetics; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Aesthetics